27.1: 13.3‐inch CAAC‐IGZO‐FET OLED Display with Narrow Driver Area Using Highly Efficient Deep Blue Device. Issue 1 (1st July 2013) - Suzuki, Tsunenori; Isa, Toshiyuki; Eguchi, Shingo; Ogita, Kaori; Kataishi, Riho; Nonaka, Yusuke; Nakashima, Harue; Sasaki, Toshiki; Seo, Satoshi; Kawashima, Susumu; Miyake, Hiroyuki; Hirakata, Yoshiharu; et al.
Abstract: We succeeded in developing a deep blue fluorescent OLED exhibiting extremely high external quantum efficiency and a long lifetime by adopting an amine‐free material to the hole transporting layer. We have also developed a CAAC‐IGZO‐FET OLED display with a narrow driver area using this deep blue device.